Clinical Benefits And Adverse Effects Of Siwak(s. Persica) Use On Periodontal Health: A Scoping Review Of Literature - Haslinda Ramli; Tuti Ningseh Mohd‑Dom; Shahida Mohd‑Said (BioMed Central Ltd, 2024)
Indexed by WOS/Scopus/ERA